Physical aspects of care. - Paice, Judith A. (HPNA palliative nursing manuals, 2015)
Palliative care is an essential element of our health care system and becoming increasingly significant amidst an aging society and organizations struggling to provide both compassionate and cost effective care. Palliative care is also characterized by a strong interdisciplinary approach. Nurses are at the centre of the palliative care team across settings and populations. The third volume in the 'HPNA Palliative Nursing Manuals' series, this book provides an overview of the principles of symptom assessment and management for symptoms including: fatigue, anorexia and cachexia, artificial nutrition and hydration, urinary tract disorders, lymphedema, skin disorders such as pressure ulcers, wounds, fistulas, and stomas, pruritus, fever, sweats, neurological disorders, anxiety and depression, and insomnia.